Multifunctional lignite fire coal catalyst and preparation and application thereof
By preparing multifunctional lignite coal-fired catalysts and using specific formulas and processes, the problems of low calorific value of lignite and high ash and sulfur content are solved, which significantly improves combustion efficiency and environmental protection effect.
Patent Information
- Application Number
- CN202510046895.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-08
AI Technical Summary
The low calorific value of lignite and high ash and sulfur contents lead to low combustion efficiency, serious environmental pollution, and large equipment losses. The existing suppression methods have problems such as incomplete desulfurization effect, high cost or secondary pollution.
The multifunctional lignite coal-fired catalyst is used, consisting of sodium carbonate, potassium carbonate, copper oxide, hematite, etc. It can improve the calorific value of lignite and inhibit the emission of ash and sulfur through specific formula design and process treatment.
It significantly improves the combustion efficiency of lignite, reduces sulfur dioxide and ash emissions, reduces environmental pollution and equipment losses, and improves energy utilization efficiency.
Smart Images

Figure BDA0005238730880000071 
Figure BDA0005238730880000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of energy chemical industry, and in particular to a method for preparing a multifunctional lignite-fired catalyst. Background Art
[0002] In the energy field, lignite, as an important coal resource, has unique properties and application challenges. Lignite has significant characteristics and its calorific value is relatively low, which means that the energy released during the combustion process is limited, resulting in low energy utilization efficiency. At the same time, lignite has high ash and sulfur content, which brings a series of serious problems. First, the high ash content increases the residue after combustion, which not only increases the processing cost, but also may cause blockage and wear of the combustion equipment, affecting the normal operation and service life of the equipment. Secondly, a large amount of ash absorbs heat during the combustion process, reduces the combustion temperature, and further affects the combustion efficiency and energy output. The presence of sulfur brings multiple hazards. During the combustion process, sulfur is converted into harmful gases such as sulfur dioxide. These gases are discharged into the atmosphere and may cause acid rain, which is extremely harmful to the ecological environment and human health. At the same time, the combustion products of sulfur will corrode the combustion equipment, shorten the service life of the equipment, and increase the cost of maintenance and replacement. In view of the problem of high ash and sulfur content in lignite, the suppression methods in the prior art have many shortcomings. Although some traditional desulfurization methods can reduce the sulfur content to a certain extent, they often have problems such as incomplete desulfurization effect, high cost or secondary pollution. For ash treatment, common methods such as physical screening can reduce some ash, but cannot fundamentally solve the impact of ash on combustion efficiency and equipment.
[0003] The technical problem to be solved by the present invention is aimed at the characteristics of the above-mentioned lignite and the defects of the existing inhibition methods. It is intended to provide a new method for preparing a multifunctional lignite coal-fired catalyst, and the catalyst prepared by this method can significantly improve the combustion efficiency of lignite and reduce the adverse effects of ash and sulfur. The catalyst of the present invention effectively improves the calorific value of lignite, so that the same mass of lignite releases more energy, thereby improving the efficiency of energy utilization. At the same time, a specific formula design is adopted, and partially soluble substances that can desulfurize or remove dust are selected to achieve effective inhibition of sulfur and ash. In terms of desulfurization, the catalyst of the present invention promotes the conversion of sulfur into more stable and harmless substances during the combustion process, thereby reducing the emission of harmful gases such as sulfur dioxide, reducing environmental pollution, and reducing corrosion to combustion equipment. In terms of dust removal, the catalyst can make the ash form a more easily handled form during the combustion process, reduce its blockage and wear on the combustion equipment, and reduce the cost of residue treatment. In summary, the multifunctional lignite-fired coal catalyst preparation method of the present invention is committed to solving a series of technical problems such as low combustion efficiency, serious environmental pollution, and large equipment loss caused by the low calorific value of lignite and high ash and sulfur content, and provides an innovative and effective solution for the efficient and clean utilization of lignite. Summary of the invention
[0004] The purpose of the present invention is to provide a multifunctional lignite-fired coal catalyst and a preparation method thereof, so as to significantly improve the combustion efficiency of lignite and effectively reduce the emission of ash and sulfur during the combustion process.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] The multifunctional lignite coal-fired catalyst provided by the present invention is composed of the following raw materials in parts by weight:
[0007] Sodium carbonate 5-10 parts
[0008] Potassium carbonate 10-15 parts
[0009] Copper oxide 5-10 parts
[0010] Hematite 10-15 parts
[0011] Manganese oxide 5-10 parts
[0012] 5-10 parts of magnesium oxide
[0013] Calcium oxide 10-15 parts
[0014] Calcium hydroxide 5-10 parts
[0015] Ammonium chloride 5-10 parts
[0016] 15-20 parts of bentonite
[0017] The preparation method of the multifunctional lignite-fired coal catalyst comprises the following steps:
[0018] Grind sodium carbonate, potassium carbonate, copper oxide, hematite, manganese oxide, magnesium oxide, calcium oxide, calcium hydroxide and ammonium chloride into 100-200 mesh respectively and set aside.
[0019] Mix the crushed raw materials and bentonite evenly according to the proportion.
[0020] Add appropriate amount of water to the mixed materials and stir into a paste.
[0021] The paste was extruded through an extruder to form granules with a diameter of 2-5 mm.
[0022] The particles are dried at a temperature of 100-150° C. for 2-4 hours, and then calcined at a temperature of 400-600° C. for 2-3 hours to obtain a finished multifunctional lignite-fired catalyst.
[0023] According to tests, the catalyst can improve the combustion efficiency of lignite by 20%, reduce sulfur dioxide emissions by 30%, and reduce ash emissions by 25%. In short, the multifunctional lignite-fired coal catalyst preparation method of the present invention is committed to solving the technical problems of low combustion efficiency, serious environmental pollution, and large equipment loss caused by low calorific value, high ash and sulfur content of lignite, and provides an innovative and effective solution for the efficient and clean utilization of lignite.
[0024] Compared with the prior art, the present invention has the following advantages and gain effects:
[0025] 1. Xinjiang has a vast territory and hematite is widely distributed, which provides sufficient raw material basis for the mining and processing of hematite and can meet long-term and stable market supply.
[0026] 2. Hematite (mainly Fe2O3) can play the following roles in the coal combustion process:
[0027] (I) Impact on the combustion process:
[0028] (1) Catalytic combustion:
[0029] When coal burns at high temperatures, the iron ions in hematite can participate in redox reactions. For example, in the oxidation reaction of coal, Fe2O3 can be first reduced to FeO or Fe3O4, and then oxidized back to Fe2O3. This process promotes the adsorption and activation of oxygen, making the coal burn more fully. The reaction process may be as follows:
[0030] C+O2=CO2 (Fe2O3 catalyzes the reaction between oxygen and carbon)
[0031] (2) Improve combustion stability:
[0032] Adding hematite can make the coal combustion process more stable because it can regulate the combustion rate and avoid local overheating or incomplete combustion during the combustion process. For example, in fluidized bed combustion, hematite can make the contact between coal particles and air more uniform, thus making the combustion more stable and reducing the flickering and extinction of the flame.
[0033] (II) Impact on desulfurization
[0034] (1) Direct desulfurization reaction:
[0035] Hematite can participate in the desulfurization process to a certain extent. At high temperatures, the iron in hematite can react with sulfur dioxide produced by coal combustion. The possible reaction mechanism is Fe2O3+3SO2+O2=2Fe2(SO4)3. The generated iron sulfate is relatively stable, thus reducing the emission of sulfur dioxide into the atmosphere.
[0036] (2) Indirect desulfurization:
[0037] Hematite promotes the complete combustion of coal and reduces the amount of reducing gases (such as carbon monoxide, hydrogen, etc.) produced by incomplete combustion. Under certain conditions, these reducing gases may react with sulfur in coal to produce sulfur-containing gases such as hydrogen sulfide, which increases the difficulty of desulfurization. Hematite makes combustion more complete, which indirectly reduces the difficulty of desulfurization.
[0038] Significantly improve the combustion efficiency of lignite, make lignite burn more completely, and reduce coal consumption.
[0039] (III) Impact on dust removal
[0040] (1) Change the ash properties:
[0041] Hematite can change the physical and chemical properties of coal ash. It can enhance the agglomeration between coal ash particles. For example, the iron ions in hematite can react chemically with some components in coal ash, causing the surface charge of coal ash particles to change, thereby promoting the aggregation of particles. When particles become larger, they are more easily captured in dust removal equipment (such as cyclone dust collectors, bag dust collectors, etc.).
[0042] (2) Reduce the generation of fine particles:
[0043] Because hematite promotes the full combustion of coal and reduces the generation of unburned carbon particles (carbon black). Carbon black is a fine particulate matter that is difficult to remove by dust removal equipment. By reducing the generation of carbon black, the emission of fine particulate matter is reduced from the source, which helps to improve dust removal efficiency.
[0044] 3. The raw materials used are low in cost, the preparation method is simple, and it is easy to produce on a large scale. DETAILED DESCRIPTION
[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0046] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0047] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0048] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0049] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0050] Example 1
[0051] Weigh 5g of sodium carbonate, 10g of potassium carbonate, 5g of copper oxide, 10g of hematite, 5g of manganese oxide, 5g of magnesium oxide, 10g of calcium oxide, 5g of calcium hydroxide, 5g of ammonium chloride, and 15g of bentonite. Crush each raw material except bentonite to 100 mesh, and then mix them evenly with bentonite. Add 115mL of water to the mixture and stir it into a paste. Extrude the paste through an extruder to form particles with a diameter of 2mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 400°C for 2 hours to obtain a multifunctional lignite-fired coal catalyst product.
[0052] Example 2
[0053] Weigh 5g of sodium carbonate, 10g of potassium carbonate, 5g of copper oxide, 10g of hematite, 5g of manganese oxide, 5g of magnesium oxide, 10g of calcium oxide, 5g of calcium hydroxide, 5g of ammonium chloride, and 15g of bentonite. Crush each raw material except bentonite to 100 mesh, and then mix them evenly with bentonite. Add 115mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 2mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 450°C for 2 hours to obtain a multifunctional lignite-fired coal catalyst finished product (calcination temperature).
[0054] Example 3
[0055] Weigh 5g of sodium carbonate, 10g of potassium carbonate, 5g of copper oxide, 10g of hematite, 5g of manganese oxide, 5g of magnesium oxide, 10g of calcium oxide, 5g of calcium hydroxide, 5g of ammonium chloride, and 15g of bentonite. Crush each raw material except bentonite to 100 mesh, and then mix them evenly with bentonite. Add 115mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 2mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2 hours to obtain a multifunctional lignite-fired coal catalyst finished product (calcination temperature).
[0056] Example 4
[0057] Weigh 5g of sodium carbonate, 10g of potassium carbonate, 5g of copper oxide, 10g of hematite, 5g of manganese oxide, 5g of magnesium oxide, 10g of calcium oxide, 5g of calcium hydroxide, 5g of ammonium chloride, and 15g of bentonite. Crush each raw material except bentonite to 100 mesh, and then mix them evenly with bentonite. Add 115mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 2mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 550°C for 2 hours to obtain a multifunctional lignite-fired coal catalyst finished product (calcination temperature).
[0058] Example 5
[0059] Weigh 5g of sodium carbonate, 10g of potassium carbonate, 5g of copper oxide, 10g of hematite, 5g of manganese oxide, 5g of magnesium oxide, 10g of calcium oxide, 5g of calcium hydroxide, 5g of ammonium chloride, and 15g of bentonite. Crush each raw material except bentonite to 100 mesh, and then mix them evenly with bentonite. Add 115mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 2mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 600°C for 2 hours to obtain a multifunctional lignite-fired coal catalyst finished product (calcination temperature).
[0060] Example 6
[0061] Weigh 5g of sodium carbonate, 10g of potassium carbonate, 5g of copper oxide, 10g of hematite, 5g of manganese oxide, 5g of magnesium oxide, 10g of calcium oxide, 5g of calcium hydroxide, 5g of ammonium chloride, and 15g of bentonite. Crush each raw material except bentonite to 100 mesh, and then mix them evenly with bentonite. Add 115mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 2mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2.5 hours to obtain a multifunctional lignite-fired coal catalyst finished product (calcination temperature).
[0062] Example 7
[0063] Weigh 5g of sodium carbonate, 10g of potassium carbonate, 5g of copper oxide, 10g of hematite, 5g of manganese oxide, 5g of magnesium oxide, 10g of calcium oxide, 5g of calcium hydroxide, 5g of ammonium chloride, and 15g of bentonite. Crush each raw material except bentonite to 100 mesh, and then mix them evenly with bentonite. Add 115mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 2mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 3 hours to obtain a multifunctional lignite-fired coal catalyst finished product (calcination temperature).
[0064] Example 8
[0065] Weigh 8g of sodium carbonate, 12g of potassium carbonate, 8g of copper oxide, 12g of hematite, 8g of manganese oxide, 8g of magnesium oxide, 12g of calcium oxide, 8g of calcium hydroxide, 8g of ammonium chloride, and 18g of bentonite. Crush each raw material except bentonite to 150 mesh, and then mix them evenly with bentonite. Add 150mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 3mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2.5 hours to obtain a multifunctional lignite-fired coal catalyst product.
[0066] Example 9
[0067] Weigh 10g of sodium carbonate, 15g of potassium carbonate, 10g of copper oxide, 15g of hematite, 10g of manganese oxide, 10g of magnesium oxide, 15g of calcium oxide, 10g of calcium hydroxide, 10g of ammonium chloride, and 20g of bentonite. Crush each raw material except bentonite to 200 mesh, and then mix them evenly with bentonite. Add 120mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 5mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2.5 hours to obtain a multifunctional lignite-fired coal catalyst product.
[0068] Example 10
[0069] Weigh 7g of sodium carbonate, 12g of potassium carbonate, 8g of copper oxide, 12g of hematite, 7g of manganese oxide, 8g of magnesium oxide, 12g of calcium oxide, 8g of calcium hydroxide, 8g of ammonium chloride, and 18g of bentonite. Crush each raw material except bentonite to 180 mesh, and then mix them evenly with bentonite. Add 130mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 5mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2.5 hours to obtain a multifunctional lignite-fired coal catalyst product.
[0070] Embodiment 11
[0071] Weigh 8g of sodium carbonate, 14g of potassium carbonate, 9g of copper oxide, 11g of hematite, 8g of manganese oxide, 6g of magnesium oxide, 13g of calcium oxide, 8g of calcium hydroxide, 7g of ammonium chloride, and 16g of bentonite. Crush each raw material except bentonite to 150 mesh, and then mix them evenly with bentonite. Add 135mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 5mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2.5 hours to obtain a multifunctional lignite-fired coal catalyst product.
[0072] Example 12
[0073] Weigh 9g of sodium carbonate, 13g of potassium carbonate, 12g of copper oxide, 13g of hematite, 8g of manganese oxide, 6g of magnesium oxide, 11g of calcium oxide, 6g of calcium hydroxide, 6g of ammonium chloride, and 16g of bentonite. Crush each raw material except bentonite to 200 mesh, and then mix them evenly with bentonite. Add 120mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 5mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2.5 hours to obtain a multifunctional lignite-fired coal catalyst product.
[0074] Embodiment 13
[0075] Weigh 5g of sodium carbonate, 11g of potassium carbonate, 6g of copper oxide, 12g of hematite, 11g of manganese oxide, 8g of magnesium oxide, 13g of calcium oxide, 8g of calcium hydroxide, 8g of ammonium chloride, and 18g of bentonite. Crush each raw material except bentonite to 200 mesh, and then mix them evenly with bentonite. Add 120mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 5mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2.5 hours to obtain a multifunctional lignite-fired coal catalyst product.
[0076] Embodiment 14
[0077] Weigh 6g of sodium carbonate, 13g of potassium carbonate, 8g of copper oxide, 13g of hematite, 10g of manganese oxide, 6g of magnesium oxide, 11g of calcium oxide, 7g of calcium hydroxide, 8g of ammonium chloride, and 18g of bentonite. Crush each raw material except bentonite to 200 mesh, and then mix them evenly with bentonite. Add 120mL of water to the mixture and stir into a paste. Extrude the paste through an extruder to form particles with a diameter of 5mm. Dry the particles at a temperature of 100°C for 2 hours, and then calcine at a temperature of 500°C for 2.5 hours to obtain a multifunctional lignite-fired coal catalyst product.
[0078] Comparative Example 1
[0079] The process and conditions are the same as those in Example 14, except that hematite is not added. Other aspects are the same as those in Example 14, to demonstrate the coal-saving, sulfur-fixing and dust-removing effects of hematite.
[0080] Comparative Example 2
[0081] The lignite is burned directly without any catalyst.
[0082] The multifunctional lignite-fired catalysts prepared in Examples 1-14, the catalyst of Comparative Example 1 and Comparative Example 2 (blank control) were respectively applied to a lignite combustion experiment of the same mass to measure the combustion efficiency, ash content and sulfur content.
[0083] The combustion efficiency is measured with reference to the national standard GB / T10180-2017 "Industrial Boiler Thermal Performance Test Procedure": This standard specifies the detailed method for industrial boiler thermal efficiency testing. The combustion efficiency is determined by the positive balance method (directly measuring the input heat and output heat to calculate the efficiency) and the reverse balance method (calculating the efficiency by measuring various heat losses).
[0084] The national standard for testing the ash content of coal during combustion in a boiler is GB / T212-2001 "Industrial Analysis Methods for Coal". The slow ash method (arbitration method) is used, and the specific operating steps are as follows:
[0085] Weigh 1±0.1g of air-dried coal sample with a particle size less than 0.2mm, accurate to 0.0002g, and place it in an ash dish that has been pre-burned to a constant mass. Place the ash dish in a muffle furnace with a temperature not exceeding 100℃, and slowly heat it to 500℃ in 30 minutes under the conditions of natural ventilation and a gap of about 15mm in the furnace door. After maintaining this temperature for 30 minutes, continue to heat it to 815℃±10℃, then close the furnace door and burn it at this temperature for 1 hour. Take out the ash dish from the furnace, place it on a heat-resistant porcelain plate or asbestos board, cool it in the air for about 5 minutes, move it into a dryer and cool it to room temperature (about 20 minutes) before weighing it.
[0086] The national standard for testing the sulfur content of coal during combustion in a boiler is GB / T214-2007 "Determination of total sulfur in coal". The high-temperature combustion neutralization method is used, and the specific operation is as follows:
[0087] The coal sample is burned in an oxygen flow at 1200℃ and kept at 1200℃±5℃ to convert the sulfur in the coal into sulfur dioxide and sulfur trioxide, which are then absorbed by hydrogen peroxide solution. The generated sulfuric acid is neutralized and titrated with a standard sodium hydroxide solution, and the total sulfur content in the coal is calculated based on the consumption of the standard sodium hydroxide solution.
[0088] The results are shown in the following table, indicating that the multifunctional lignite-fired catalysts prepared in Examples 1-14 can significantly improve the combustion efficiency of lignite, reduce ash and sulfur emissions (relative to Comparative Example 2), and the effect is better than the catalyst in Comparative Example 1.
[0089]
[0090]
[0091] It can be seen from the above experimental results that the coal-saving catalyst prepared by the present invention has significant coal-saving, sulfur-fixing and dust-removing effects.
[0092] The above-described embodiments are merely descriptions of preferred embodiments of the present invention, and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by those skilled in the art should fall within the scope of protection defined by the claims of the present invention.
Claims
1. A multifunctional lignite coal-fired catalyst, characterized in that : The multifunctional lignite coal-fired catalyst is composed of the following raw materials in parts by weight: 5-10 parts of sodium carbonate, 10-15 parts of potassium carbonate, 5-10 parts of copper oxide, 10-15 parts of hematite, 5-10 parts of manganese oxide, 5-10 parts of magnesium oxide, 10-15 parts of calcium oxide, 5-10 parts of calcium hydroxide, 5-10 parts of ammonium chloride, and 15-20 parts of bentonite.
2. The multifunctional lignite-fired catalyst according to claim 1, characterized in that : The multifunctional lignite-fired catalyst is preferably composed of the following raw materials in parts by weight: 7-9 parts of sodium carbonate, 13-15 parts of potassium carbonate, 7-8 parts of copper oxide, 13-15 parts of hematite, 8-10 parts of manganese oxide, 8-10 parts of magnesium oxide, 13-14 parts of calcium oxide, 7-9 parts of calcium hydroxide, 6-8 parts of ammonium chloride, and 18-20 parts of bentonite.
3. A method for preparing the multifunctional lignite-fired catalyst according to claim 1 or 2, characterized in that: The following steps are involved: 1) crushing sodium carbonate, potassium carbonate, copper oxide, hematite, manganese oxide, magnesium oxide, calcium oxide, calcium hydroxide and ammonium chloride to 100-200 mesh (preferably 150-180 mesh) respectively for standby use; 2) Mixing the crushed raw materials and bentonite uniformly in the required proportion; 3) Add an appropriate amount of water (100-130 parts by weight based on 15-20 parts by weight of the raw material bentonite) to the mixed materials and stir into a paste; 4) Extruding the paste through an extruder to form particles with a diameter of 2-5 mm; 5) Dry the particles at 100-150° C. for 2-4 hours, and then calcine at 400-600° C. (preferably 500-550° C.) for 2-3 hours (preferably 2.5-3 hours) to obtain a multifunctional lignite-fired catalyst product.
4. Use of the catalyst according to claim 1 or 2 as a catalyst for burning lignite.
5. The use according to claim 4, characterized in that: The multifunctional lignite coal-burning catalyst is added to the lignite raw coal as a coal-saving catalyst, and the amount of the added catalyst is in the range of 0.08-0.12% (preferably 0.10%-0.12%) of the mass of the raw coal.